1989
DOI: 10.1073/pnas.86.14.5237
|View full text |Cite
|
Sign up to set email alerts
|

The (A)BC excinuclease of Escherichia coli has only the UvrB and UvrC subunits in the incision complex.

Abstract: The uvrA, uvrB, and uvrC genes control excision repair in Escherichia coli. Cells with mutations in any of these three genes cannot repair DNA by nucleotide excision. When the purified gene products-the UvrA, UvrB, and UvrC proteins-are mixed together, an excision nuclease is formed that incises on both sides of the damaged nucleotide in an ATP-dependent reaction; it has been presumed that the excision nuclease was an ABC complex containing all three Uvr proteins. To determine the stoichiometry of the subunits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
206
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(217 citation statements)
references
References 16 publications
9
206
2
Order By: Relevance
“…15, January 2004also required for the 3Ј incision (Orren and Sancar, 1989;Verhoeven et al, 2000). UvrB is thought to stabilize the UvrC-DNA contacts.…”
Section: Slx1-slx4 Endonucleasementioning
confidence: 99%
“…15, January 2004also required for the 3Ј incision (Orren and Sancar, 1989;Verhoeven et al, 2000). UvrB is thought to stabilize the UvrC-DNA contacts.…”
Section: Slx1-slx4 Endonucleasementioning
confidence: 99%
“…Hydrodynamic studies that I performed in Aziz's lab showed that UvrB and UvrC in isolation were monomeric, while UvrA alone formed dimers (Orren and Sancar, 1989). Mixtures of the proteins in the absence of DNA revealed a (UvrA) 2 UvrB complex, and UvrC did not associate with this complex or with UvrA or UvrB alone (Orren and Sancar, 1989).…”
Section: Contributions To Understanding Prokaryotic Ner: Biochemical mentioning
confidence: 99%
“…Hydrodynamic studies that I performed in Aziz's lab showed that UvrB and UvrC in isolation were monomeric, while UvrA alone formed dimers (Orren and Sancar, 1989). Mixtures of the proteins in the absence of DNA revealed a (UvrA) 2 UvrB complex, and UvrC did not associate with this complex or with UvrA or UvrB alone (Orren and Sancar, 1989). UvrA was shown to be instrumental in DNA damage recognition, with higher affinity to damaged than to undamaged DNA, a difference that was further stimulated by ATP; UvrA bound to a 33 bp region surrounding a psoralen adduct (Seeberg and Steinum, 1982;Van Houten et al, 1987;Yeung et al, 1986).…”
Section: Contributions To Understanding Prokaryotic Ner: Biochemical mentioning
confidence: 99%
“…UvrA 2 -UvrB 1 complexes recognize DNA damage. Then, the UvrA proteins dissociate from the UvrB-DNA complex, and a UvrC protein binds to the UvrB-DNA complex (15), leading to incisions on either side of the damage. Finally, the UvrD helicase removes the damaged region.…”
Section: Analysis Of Recombination Junctions In Uv-induced Bio-transdmentioning
confidence: 99%